Helical Tomotherapy for the Treatment of Anal Canal Cancer: A Dosimetric Comparison with 3D Conformal Radiotherapy. Issue 3 (May 2015) - Ugurluer, Gamze; Ballerini, Giorgio; Moeckli, Raphael; Matzinger, Oscar; Bourhis, Jean; Ozsahin, Mahmut
Aims and Background: The standard treatment of anal canal cancer (ACC) is combined chemotherapy and radiation therapy (RT), which is complex because of the shape of the target volumes and the need to minimize the irradiation of normal pelvic structures. In this study we compared the dosimetric results of helical tomotherapy (HT) plans with traditional 3D conformal RT (3DRT) plans for the treatment of ACC. Methods and Study Design: Twelve patients (median age 57 years, range 38–83; F/M 8/4) treated with HT and concurrent chemotherapy for locally advanced ACC were selected. All had histologically confirmed squamous-cell carcinoma. A clinical target volume including the tumor and pelvic and inguinal lymph nodes was treated with HT to a total dose of 36 Gy in 1.8-Gy daily fractions. Then a sequential boost of 23.4 Gy in 1.8-Gy daily fractions (total dose 59.4 Gy) was delivered to the tumor and involved nodes. For all 12 patients, 3DRT plans were generated for comparison. Treatment plans were evaluated by means of standard dose-volume histograms. Dose coverage of the planning target volumes (PTVs), homogeneity index (HI), and mean doses to organs at risk (OARs) were compared. Results: The coverage of PTV was comparable between the two treatment plans. HI was better in the HT vs. 3DRT plans (1.25 and 3.57, respectively; p<0.0001). HT plans resulted in better sparing of OARs (p<0.0001). Conclusions: HT showed superior target dose conformality and significant sparing of pelvic structures compared with 3DRT. Further investigation should determine if these dosimetric improvements will improve clinical outcomes regarding locoregional control, survival, and treatment-related acute and late morbidity.